OSCS (One Step Conservative Surgery) vs MOSCUS (Modified One Step Conservative Uterine Surgery) for Placenta Accreta Spectrum (PAS) Surgery, Which One Is More Preferred? A Literature Review - Cantika Anakita; Arya Marganda Simanjuntak; Donel S.; Noviardi Noviardi; Renardy Reza Razali (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Placenta Accreta Spectrum (PAS) is a severe obstetric complication causing hemorrhage, maternal morbidity, and mortality. Two widely adopted approaches to treatment are OSCS and MOSCUS. This literature review compares OSCS and MOSCUS to provide evidence-based insights for optimizing PAS treatment.Objective: This study aims to compare the preferred conservative uterine surgical approaches in the management of Placenta Accreta Spectrum (PAS).Methods: A literature review was undertaken following the scale assessment of narrative review articles (SANRA). We utilized various databases to evaluate current evidence for OSCS and MOSCUS in treating PAS. Relevant articles were reviewed to perform a comparative analysis between OSCS and MOSCUS in order to address the objective.Result: The key difference between OSCS and MOSCUS lies in bleeding control by optimal uterine reconstruction with transverse b-lynch suture and selective vascular ligation. While OSCS is ideal for simpler cases due to its efficiency and practicality, MOSCUS is better suited for complex PAS cases, offering reduced complications and improved outcomes.Conclusion: MOSCUS may be preferable to OSCS in terms of technique with optimal uterine reconstruction by adding several techniques to potentially preserve the uterus. More comparative research between the two required to evaluate the results prospectively. AbstrakPendahuluan: Placenta Accreta Spectrum (PAS) merupakan komplikasi obstetri berat yang menyebabkan perdarahan, morbiditas dan mortalitas ibu. Dua pendekatan yang banyak diadopsi adalah OSCS dan MOSCUS. Tinjauan literatur ini membandingkan OSCS dan MOSCUS untuk memberikan wawasan berbasis bukti untuk mengoptimalkan tatalaksana PASTujuan: Penelitian ini bertujuan untuk membandingkan pilihan tindakan bedah uterus konservatif yang lebih disukai dalam penatalaksanaan Placenta Accreta Spectrum (PAS).Metode: Metode yang digunakan dalam penelitian ini adalah tinjauan literatur yang mengikuti penilaian kualitas SANRA. Kami menggunakan berbagai basis data untuk mengevaluasi bukti terkini OSCS dan MOSCUS dalam tatalaksana PAS. Artikel didiskusikan untuk membuat tinjauan yang komprehensif dan membuat analisis komparatif antara OSCS dan MOSCUS untuk menjawab tujuan penelitian.Hasil: Perbedaan antara OSCS dan MOSCUS bergantung pada kontrol perdarahan dengan rekonstruksi uterus yang optimal dengan jahitan b-lynch melintang dan ligasi pembuluh darah selektif. OSCS ideal untuk kasus-kasus yangKesimpulan: MOSCUS dapat menjadi pilihan dibandingkan dengan OSCS dalam hal teknik dengan rekonstruksi rahim yang optimal dengan menambahkan beberapa teknik yang berpotensi mempertahankan rahim. Penelitian komparatif lebih lanjut antara keduanya diperlukan untuk mengevaluasi hasilnya secara prospektif.